2023
DOI: 10.1088/2058-9565/ace54a
|View full text |Cite
|
Sign up to set email alerts
|

Meta-learning digitized-counterdiabatic quantum optimization

Abstract: The use of variational quantum algorithms for optimization tasks has emerged as a crucial application for the current noisy intermediate-scale quantum computers. However, these algorithms face significant difficulties in finding suitable ansatz and appropriate initial parameters. In this paper, we employ meta-learning using recurrent neural networks to address these issues for the recently proposed digitized-counterdiabatic quantum approximate optimization algorithm. By combining meta-learning and counterdiaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…The performance of CD-QAOA depends on the choice of initial parameters and classical optimizers. Reinforcement learning was used for optimization [98], and a meta-learning technique using recurrent neural networks was considered for initial parameter setting [101]. As another development, the power of single-layer QAOA [102] and improvement by higher-order counterdiabatic terms [103] were confirmed, and the theory was extended to photonic systems with continuous variables [104].…”
Section: Performance Improvementmentioning
confidence: 99%
“…The performance of CD-QAOA depends on the choice of initial parameters and classical optimizers. Reinforcement learning was used for optimization [98], and a meta-learning technique using recurrent neural networks was considered for initial parameter setting [101]. As another development, the power of single-layer QAOA [102] and improvement by higher-order counterdiabatic terms [103] were confirmed, and the theory was extended to photonic systems with continuous variables [104].…”
Section: Performance Improvementmentioning
confidence: 99%
“…However, practical implementation often requires speeding up adiabatic evolution, leading to various approaches like shortcuts to adiabaticity (STA) [34,35], including fast-forward methods, invariant-based inverse engineering, and counterdiabatic (CD) protocols, which is the main focus of this study. Readers interested in more detailed developments on quantum optimization processes for CD protocols and direct applications are directed to works such as [36,37] (as well as references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the trade-off between circuit depth and performance, constrained by coherence times in existing and near-term quantum processors, poses a significant challenge [19,20,21,22]. Additionally, the complexity introduced by the QAOA ansatz, with its increasing number of variational parameters, presents challenges for classical optimizers [23,24,25]. Previous studies have shown that the optimal QAOA parameters exhibit specific patterns [26,27], leading to depth-sequential strategies and machine learning-based methods for parameter initialization [10,23,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the complexity introduced by the QAOA ansatz, with its increasing number of variational parameters, presents challenges for classical optimizers [23,24,25]. Previous studies have shown that the optimal QAOA parameters exhibit specific patterns [26,27], leading to depth-sequential strategies and machine learning-based methods for parameter initialization [10,23,28,29,30]. For instance, Alam et al adopted a regression model to predict high-depth parameters from low-depth ones [26], while Amosy et al applied iterative neural networks for parameter initialization, selecting the most promising parameter sets from cluster centers for the given problem [31].…”
Section: Introductionmentioning
confidence: 99%